2010
DOI: 10.1007/s10654-010-9500-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for otitis media in children with special emphasis on the role of colonization with bacterial airway pathogens: the Generation R study

Abstract: Acute otitis media is the most frequent diagnosis in children visiting physicians’ offices. Risk factors for otitis media have been widely studied. Yet, the correlation between bacterial carriage and the development of otitis media is not entirely clear. Our aim was to study in a population-based prospective cohort the risk factors for otitis media in the second year of life with special emphasis on the role of colonization with Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Like the higher rate of overcrowding, we have previously reported a higher rate of middle ear disease, detected using CHCs, in remote communities compared with the urban IIHS (5.5 times) (Spurling et al 2012). This study's findings regarding the association between middle ear disease and previous episodes of ear infection and increasing household number are consistent with large international cohort studies (Labout et al 2011), one of which also identified low socioeconomic status as a risk factor (Paradise et al 1997). However, our findings differ from the two other epidemiological studies involving Aboriginal populations in rural and remote areas (Jacoby et al 2008;Bailie et al 2010) and a meta-analysis examining risk factors for middle ear disease (Uhari et al 1996), which found that environmental tobacco smoke and childcare attendance were important risk factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Like the higher rate of overcrowding, we have previously reported a higher rate of middle ear disease, detected using CHCs, in remote communities compared with the urban IIHS (5.5 times) (Spurling et al 2012). This study's findings regarding the association between middle ear disease and previous episodes of ear infection and increasing household number are consistent with large international cohort studies (Labout et al 2011), one of which also identified low socioeconomic status as a risk factor (Paradise et al 1997). However, our findings differ from the two other epidemiological studies involving Aboriginal populations in rural and remote areas (Jacoby et al 2008;Bailie et al 2010) and a meta-analysis examining risk factors for middle ear disease (Uhari et al 1996), which found that environmental tobacco smoke and childcare attendance were important risk factors.…”
Section: Discussionsupporting
confidence: 87%
“…Large birth cohort studies in the Netherlands and the United States of American (USA) found that significant predictors of otitis media at 2 years of age were male gender, otitis media in the first year of life, socioeconomic disadvantage and exposure to other children in the house (Paradise et al 1997;Labout et al 2011). Higher rates of otitis media among Aboriginal and Torres Strait Islander children have been attributed to early nasopharyngeal bacterial colonisation, chronic upper respiratory tract infections and social factors such as poverty, overcrowding and exposure to cigarette smoke (Kong and Coates 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ever vs never breastfeeding and outcome of AOM during the first 24 months was reported by five cohort studies . Four included studies’ quality ranged from ‘satisfactory’ to ‘good’ (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Using data collected from a population-based prospective birth cohort in Rotterdam in The Netherlands, researchers found no association between 3 or more months of breastfeeding and AOM in the second year of life [19]. AOM was defined by parental report of at least one occurrence of fever accompanied by earache for which a physician was visited.…”
Section: Breastfeeding and Acute Otitis Mediamentioning
confidence: 99%